Study on knowledge generation and transfer in Ethiopian agricultural researches - Chala, S. (Jimma University, 2013)
Knowledge management in the agriculture sector is about the systematic connection of all stakeholders to the best practices, knowledge and expertise they need to create value by supporting creation, acquisition, transfer and utilization of knowledge. In Ethiopia, various research institutes both national and international play significant roles in the generation and transfer of agricultural knowledge, but in the country the sector is one of the lowest levels of productivity in the world which suggests there are inadequate linkages between the Research Institutes and the practitioners. The main aim of this study was to investigate the knowledge generation and transfer practices that some Agricultural Research Institutes in Ethiopia have in place and assess the affecting factors involved in these processes. A mixed methods research methodology encompassing a questionnaire and interviews was used to achieve this objective. Quantitative data were collected using questionnaires from both research institutes, higher educational institutes and their stakeholders using SurveyMonkey. Qualitative data were collected by means of interviews which were conducted with 15 key informants from both the research institutes and the stakeholders. The finding of this study indicates that in Ethiopia not all agricultural researchers and institutes fully perform end user demand analysis before generating and transferring agricultural knowledge. It was also found that most of the research institutes generate knowledge based on the government priorities and centrally identified problems. This study confirmed that researchers and their institutes did not fully carry out assessment on their research output’s impact. The study also revealed that the majority of relationship(56.9%) established between researchers and their stakeholders was not usually based on formal partnership but most of them (44.1%) meet with the stakeholders regularly mainly when stakeholders need new technology. The result of this study established that most researchers believe that the existing forms of cooperation and partnership between researchers/research institute and the stakeholders are inappropriate to boost knowledge transfer activities. Most of the researchers (58.8%) unwelcome that the research output should reach the end users indirectly through the stakeholders while majority of stakeholders (76.5%) appreciate that the agricultural research output should reach end user directly. The study finding suggests that most research institutes do not provide special incentives and rewards to researchers for transferring knowledge. Most ii | P a g e stakeholders do not think that the transferred knowledge is utilized effectively by the end users due to lack of support from researchers , the generated knowledge is not based on the demands of the users and poor linkage of research and extension. This study confirmed that there were a lot of challenges and problems faced during knowledge transfer. None demand driven research output, infrastructure, weak research extension system, researchers’ language barrier to communicate research findings, scattered nature of knowledge, absence of repository for knowledge in this country, non existence of linkage between knowledge generating institutes to get different knowledge, limited participation of stakeholders in the research institutes activities ,etc were the major. With regard to the factors affecting the transfer and acquisition of agricultural knowledge from the research institutes to stakeholders, the methods and communication tools and channels used to present new knowledge were not welladapted to the interests of stakeholders, Traditional product formats fail to reach most stakeholders were the majors established from this study. In order to make agricultural knowledge/information effectively applied and utilized by the practitioners, it is recommended that researchers should primarily specify the recipient target groups and investigate their needs through the implementation of different demand analysis techniques. To make the research institutes and stakeholders closer to each other, there should be a formal partnership established on common interest and goals with shared responsibility. The researchers have to utilize appropriate transfer mechanisms which can best allow actors (i.e. researchers, Transfer agents and practitioners) to exchange knowledge and information and its impact should be assessed to take any actions needed. Eventually, to make the knowledge generation, transfer and acquisition more effective and efficient, the government should adopt policy dimensions which can create efficient institutional setup, the organizational structure of both stakeholders and research institutes should be also revised in a way that support this efforts, there should be improvements among all parties in utilizing their resources efficiently, and the research institutes and their stakeholders should have a clear strategy of how to create, capture and transfer agricultural knowledge.